EXPOSURE TO METHYL METHACRYLATE UPREGULATES THE EXPRESSION OF INOS IN THE TONGUE TISSUE OF RATS EXPERIMENTAL MODEL - Alzarea BK (European Scientific Journal, ESJ, 2014)
Methyl methacrylate is widely used particularly in dental laboratories and its toxicity is a matter of concern. The aim of the present study was to investigate the effects of exposure to MMA through the expression of iNOS in tongue tissue. The present study involved the exposure of Wister rats to 0.2 mg/kg body weight for 30 days. Two groups of animals (N=10 for each group) and assigned as control group and test group. After the end of the experiment, animals were terminated and tongue tissue was used to investigate the expression of iNOS using indirect immunohistochemistry. Slides were assessed using adopy photoshop software. Photos for sections were taken and divided into pixels. The total number of pixels was computed and represented both colours (blue and brown), then the brown colour (the colour of the marker under study) was computed and divided by the total number of pixels. Study findings revealed significant expression of iNOS in test group compared with control group (P 0.000). Taken together, previous studies targeting the effects of exposure to MMA pointed to some inflammatory conditions without exploring molecular mechanisms underlying these effects. The present study showed toxic effects of exposure to MMA through upregulation of iNOS in tongue tissue of rats exposed to MMA. These findings may be the first to explore this aspect.